Evaluación y propuesta de tratamiento de efluentes residuales del Camal municipal de la ciudad de Moyobamba - Nuñez Tinoco, Alex Nahum (2012)
This research paper was in the facilities of the municipal slaughterhouse of the Moyobamba city. Where our object study was to evaluate the quality of the residual effluent discharged to the environment and propose a treatment system for the same. Por this action was necessary to take a representative sample of the effluent quarterly, to then be analyzed and know the values of the parameters to be measured according to the objectives. The same that allowed us to contrast with the maximum allowable limits for this type of effluent standard established in the national and international regulations. The work consisted of taking three representative samples of the effluent in residual different points along the route of the effluent. The first prior to entering the septic tank, the second in the final discharge of the septic tank and the third 1 00 yards further down for the second sample. To subsequently be anályzed in the Fish & Aquaculture laboratory and then obtain the values of the parameters to be measured, the same that is systematized and evaluated. Thus enabling us to propose two systems of wastewater treatment; as reflected in the content of the present investigation. Finally, we prepared the final report of the investigation with plans and budgets of each treatment. In where is indicated which is the most feasible to run and also to make the most efficient.